Frequency of Echocardiographic Changes in Patients with Chronic Liver Disease at a Tertiary Care Hospital in Karachi: Echocardiographic Changes in Chronic Liver Disease - Bazarqa, Hafiza; Alam, Muhammad Tanveer; Kashif, Syed Muhammad; Lal, Hari; Imam, Beenish; Banu, Sabiha (Pakistan Journal of Health Sciences, 2025)
Chronic liver disease (CLD) is a major health burden in Pakistan, commonly due to viral hepatitis. Cirrhotic cardiomyopathy (CCM) is an underdiagnosed complication that may impact prognosis and management. Objectives: To determine the frequency and spectrum of echocardiographic abnormalities in CLD patients and assess their correlation with disease severity based on the Child-Pugh classification. Methods: A cross-sectional study of 187 adult CLD patients was conducted at Dr. Ruth K.M. Pfau Civil Hospital, Karachi, between September 2024 and February 2025. Echocardiographic parameters, including pulmonary artery pressure, ejection fraction, systolic, and diastolic function, were evaluated using a Philips EPIQ 7 (Philips Healthcare, Andover, MA, USA) system. Patients were categorized according to Child-Pugh class (B or C). Associations between echocardiographic findings and Child-Pugh class were analyzed using chi-square and logistic regression tests, with p < 0.05 considered significant. Results: Mean age was 55.6 ± 13.4 years; 51.9 % were men. The leading etiologies were hepatitis C (46 %) and B (26 %). Diastolic dysfunction was the most frequent abnormality (53.5 %), while systolic dysfunction occurred in 23.5 %—significantly more common in women (p < 0.001) and in advanced disease (Child-Pugh C: 67 % vs B: 38 %; OR ≈ 3.4, p=0.0001). Pulmonary hypertension (23.5%) and reduced ejection fraction (10.2%) showed no correlation with Child-Pugh class. Conclusions: Echocardiographic abnormalities are common in CLD, particularly diastolic dysfunction. Systolic dysfunction increases with worsening hepatic severity, emphasizing the need for routine cardiac assessment in cirrhotic patients for better risk stratification and management.